2003
DOI: 10.1128/jcm.41.5.1971-1976.2003
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Rhinoviruses by Nucleic Acid Sequence-Based Amplification after Nucleotide Sequence Determination of the 5′ Noncoding Regions of Additional Rhinovirus Strains

Abstract: The isothermal nucleic acid sequence-based amplification (NASBA) system was applied for the detection of rhinoviruses using primers targeted at the 5 noncoding region (5 NCR) of the viral genome. The nucleotide sequence of the 5 NCRs of 34 rhinovirus isolates was determined to map the most conserved regions and design more appropriate primers and probes. The assay amplified RNA extracted from 30 rhinovirus reference strains and 88 rhinovirus isolates, it did not amplify RNA from 49 enterovirus isolates and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Similar observations have been reported by others (19). The presence of mismatches between the target RNA and the primers and probes causes an inefficient amplification and detection, as reported previously (8,9,15,26,27). Gobbers et al (15) reported that single point mutations near the 3Ј end of the primers, closely followed by a second mismatch, seem to hamper NASBA amplification.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Similar observations have been reported by others (19). The presence of mismatches between the target RNA and the primers and probes causes an inefficient amplification and detection, as reported previously (8,9,15,26,27). Gobbers et al (15) reported that single point mutations near the 3Ј end of the primers, closely followed by a second mismatch, seem to hamper NASBA amplification.…”
Section: Discussionmentioning
confidence: 80%
“…In earlier studies, group A RVs were also detected less frequently than group B RVs (1,2,24,26,32). Although at present, a higher number of group B RVs is known than group A RVs, analysis of epidemiological data indicated that group B RVs produced more than twice as many clinical infections per serotype as group A RVs did.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, RNA is the genomic material of numerous respiratory viruses. The application of an RNA-based amplification technique offers potential advantages com- Kidd et al (1996) VA region, variable, subgenera A + RFLP Morris et al (1996) Hexon, 300 bp/243 bp, subgenus C N-A types Tiemessen and Nel (1996) Long-fiber gene, 152 bp, subgenus F A-H Avellon et al (2001) Hexon, 168 bp, polyvalent A Allard et al (2001) Hexon, 301 bp/171, typing N-A-RFLP Rhinovirus Gamma et al (1989) 5 -Non-coding region A Hyypia et al (1989) 5 -Non-coding region A + H Arruda and Hayden (1993) 5 -Non-coding region A Johnston et al (1993) 5 -Non-coding region, 900 bp A + H Santti et al (1997) 5 -Non-coding region, 126/96/533 bp A Samuelson et al (1998) 5 -Non-coding region NASBA, ECL Andeweg et al (1999) 5 -Non-coding region-VP4 N-A-H Steininger et al (2001) 5 -Non-coding region, 106/93 bp N-A Billaud et al (2003) 5 -Non-coding region, rhino v N-A Loens et al (2003a) 5 -Non-coding region NASBA-ECL Deffernez et al (2004) 5 -Non-coding region A pared to a DNA-based amplification technique: no additional reverse transcriptase step is required, thus saving time and reducing the risk of contamination. The specificity of the reactions might, however, be lower because the enzymes used are not thermostable, so that the reaction temperature may not exceed 42 • C without compromising the reaction.…”
Section: Amplification Techniquesmentioning
confidence: 99%